Bhutan : Transport Sector Note - World Bank (Washington, DC, 2013)
Landlocked Bhutan faces unique challenges, and opportunities as it pursues the development of its transport sector into the 21st century. Bhutan's population growth rate is high, rural-urban migration is accelerating, and, fueled by sustained economic growth, the country is urbanizing rapidly, giving rise to an expanding urban middle class, with rising expectations of well-paid employment, accessible services, and consumption potential. However, accessibility to a large measure depends on availability of reliable, and affordable transportation. Poor rural access is synonymous with rural isolation, and poverty, while high external and domestic transport costs constrain the country's economic and social development. Transportation poses a considerable cost disadvantage to business and commercial undertakings; road transport is slow and regularly disrupted by landslides and flooding; air transport is costly and erratic. Costly transport is a major factor constraining the development of tourism, horticultural exports, and agro-processing and wood-based industries. Sector issues discussed in this report emerge from a detailed assessment of the transport system, and an analysis of public expenditures. It discusses the strategy for improving rural accessibility, and the central role of roads, and motorized transport for integrating remote regions and communities into the national economy; access to regional and global markets, to include technical support for development, operation, and management of transport logistics, establishment of a dry port in Phuentsholing with reefer storage facilities, and, internationally competitive Druk air cargo rates, especially for exports of perishable, and high value agricultural products; transport sector planning and coordination, which includes specific policy, planning, and investment recommendations for roads, air transport, urban transport, and road transport services. It is recommended to consider recasting the proposed Transport Master Plan as a National Transport Strategy and Policy Review to identify and analyze emerging challenges, and constraints in the transport sector; recommend appropriate strategies, and policies to address these concerns; and, prepare an implementation plan for sector modernization, including policy and institutional reforms.